RANKL/RANK System-Based Mechanism for Breast Cancer Bone Metastasis and Related Therapeutic Strategies - Wu, Xiaoqiu; Li, Fangfei; Dang, Lei; Liang, Chao; Lu, Aiping; Zhang, Ge (Frontiers in Cell and Developmental Biology, 2020)
Breast cancer remains one of the most life-threatening tumors affecting women. Most patients with advanced breast cancer eventually develop metastatic diseases, which cause significant morbidity and mortality. Approximately two-thirds of patients with advanced breast cancer exhibit osteolytic-type bone metastasis, which seriously reduce the quality of life. Therefore, development of novel therapeutic strategies for treating breast cancer patients with bone metastasis is urgently required. The “seed and soil” theory, which describes the interaction between the circulating breast cancer cells (seeds) and bone microenvironment (soil), is widely accepted as the mechanism underlying metastasis. Disruption of any step in this cycle might have promising anti-metastasis implications. The interaction of receptor activator of nuclear factor-κB ligand (RANKL) and its receptor RANK is fundamental in this vicious cycle and has been shown to be a novel effective therapeutic target. A series of therapeutic strategies have been developed to intervene in this cross-talk. Therefore, in this review, we have systematically introduced the functions of the RANKL/RANK signaling system in breast cancer and discussed related therapeutic strategies.